The Making of Islamic Heritage Muslim Pasts and Heritage Presents - Rico, Trinidad (Heritage Studies in the Muslim World,, 2017)
This book is open access under a CC BY 4.0 license. Offering key insights into critical debates on the construction, management and destruction of heritage in Muslim contexts, this volume considers how Islamic heritages are constructed through texts and practices which award heritage value. It examines how the monolithic representation of Islamic heritage (as a singular construct) can be enriched by the true diversity of Islamic heritages and how endangerment and vulnerability in this type of heritage construct can be re-conceptualized. Assessing these questions through an interdisciplinary lens including heritage studies, anthropology, history, conservation, religious studies and archaeology, this pivot covers global and local examples including heritage case studies from Indonesia, Egypt, Saudi Arabia, Iran, Jordan, and Pakistan. .